Perfusion Imaging for Endovascular Thrombectomy in Acute Ischemic Stroke Is Associated With Improved Functional Outcomes in the Early and Late Time Windows. Issue 9 (4th May 2022) - Dhillon, Permesh Singh; Butt, Waleed; Podlasek, Anna; McConachie, Norman; Lenthall, Robert; Nair, Sujit; Malik, Luqman; Booth, Thomas C.; Bhogal, Pervinder; Makalanda, Hegoda Levansri Dilrukshan; Spooner, Oliver; Mortimer, Alex; et al.
Abstract : Background: The impact on clinical outcomes of patient selection using perfusion imaging for endovascular thrombectomy (EVT) in patients with acute ischemic stroke presenting beyond 6 hours from onset remains undetermined in routine clinical practice. Methods: Patients from a national stroke registry that underwent EVT selected with or without perfusion imaging (noncontrast computed tomography/computed tomography angiography) in the early (<6 hours) and late (6–24 hours) time windows, between October 2015 and March 2020, were compared. The primary outcome was the ordinal shift in the modified Rankin Scale score at hospital discharge. Other outcomes included functional independence (modified Rankin Scale score ≤2) and in-hospital mortality, symptomatic intracerebral hemorrhage, successful reperfusion (Thrombolysis in Cerebral Infarction score 2b–3), early neurological deterioration, futile recanalization (modified Rankin Scale score 4–6 despite successful reperfusion) and procedural time metrics. Multivariable analyses were performed, adjusted for age, sex, baseline stroke severity, prestroke disability, intravenous thrombolysis, mode of anesthesia (Model 1) and including EVT technique, balloon guide catheter, and center (Model 2). Results: We included 4249 patients, 3203 in the early window (593 with perfusion versus 2610 without perfusion) and 1046 in the late window (378 with perfusion versus 668 without perfusion). Within the late window, patients with perfusion imaging had a shift towards better functional outcome at discharge compared with those without perfusion imaging (adjusted common odds ratio [OR], 1.45 [95% CI, 1.16–1.83]; P =0.001). There was no significant difference in functional independence (29.3% with perfusion versus 24.8% without; P =0.210) or in the safety outcome measures of symptomatic intracerebral hemorrhage ( P =0.53) and in-hospital mortality (10.6% with perfusion versus 14.3% without; P =0.053). In the early time window, patients with perfusion imaging had significantly improved odds of functional outcome (adjusted common OR, 1.51 [95% CI, 1.28–1.78]; P =0.0001) and functional independence (41.6% versus 33.6%, adjusted OR, 1.31 [95% CI, 1.08–1.59]; P =0.006). Perfusion imaging was associated with lower odds of futile recanalization in both time windows (late: adjusted OR, 0.70 [95% CI, 0.50–0.97]; P =0.034; early: adjusted OR, 0.80 [95% CI, 0.65–0.99]; P =0.047). Conclusions: In this real-world study, acquisition of perfusion imaging for EVT was associated with improvement in functional disability in the early and late time windows compared with nonperfusion neuroimaging. These indirect comparisons should be interpreted with caution while awaiting confirmatory data from prospective randomized trials.